Adaptation and psychometric properties of Psychological Skills Inventory for Sport (PSIS-R5) in Latvian athletes: Insights and implications for practice - Katrina Volgemute; Gundega Ulme; Viktorija Perepjolkina; Renars Licis; Agita Abele; Rodrigo Lavins; Alina Klonova; Anna Tihija; Everts Grants (PLoS ONE, 2025)
Background and objective Psychological skills are critical for high achievement and elite sports performance. However, there remains a lack of valid, reliable, and accessible instruments adapted to modern athletes. This highlights significant psychometric challenges in the existing tools currently available. While the Psychological Skills Inventory for Sport (PSIS-R5) is a commonly used tool in sports psychology worldwide, it has demonstrated various psychometric issues over time. A previous adaptation to the Latvian sports environment highlighted specific challenges in the Latvian context. It is important to note that these issues are not unique to the Latvian adaptation. A comprehensive review is necessary to address these broader psychometric concerns and ensure the instrument’s suitability for contemporary athletes, including those in Latvia. Moreover, the adaptation process may offer insights and methodological guidance for similar efforts in other cultural contexts. The aims of this research were twofold: first, to review and adapt the PSIS-R5 for use in Latvia (PSIS-R5-L), ensuring its validity and reliability; and second, to assess the applicability of the PSIS-R5-L in elite sports settings by examining relationships between athletes’ achievement levels and psychological skills. Methods A total of 444 Latvian athletes aged between 18–43 (M = 21.32; SD = 6.52) completed the PSIS-R5 inventory to assess their psychological skills. The PSIS-R5 was re-translated into Latvian language (PSIS-R5-L) using forward-backward translation. Additionally, five sports psychologists participated in the study, providing evaluations of elite athletes’ psychological skills using the PSIS-R5 inventory. Results Series of Principal Components Analyses (PCA) were conducted to explore and validate the structure of the Latvian revisited adaptation of the PSIS-R5-L. As a result, a stable four-factor structure was obtained, consisting of 17 items with satisfactory fit indices (CFI = 0.968, RMSEA = 0.045 [90% CI: 0.034, 0.057], SRMR = 0.026). The findings indicate that the Latvian adapted PSIS-R5-L has appropriate psychometric properties, confirming its suitability for use in the Latvian sports environment. Comparisons between different athlete groups (elite, pre-elite, and amateur) revealed several correlations and statistically significant (p < 0.05) differences in psychological skills. Conclusions The PSIS-R5-L is a psychometrically robust and practically valuable tool for assessing athletes’ psychological skills in Latvia. It offers coaches, sports psychologists, and practitioners an evidence-based instrument to evaluate and enhance mental skills across different athlete populations, supporting psychological preparation programs in both elite and amateur sports settings.